"To go, or not to go, that is the question": perceived inaccessibility among individuals with disabilities in Shanghai. Issue 10 (26th November 2022) - Mao, Xupeng; Chen, Lin
Abstract: This study explored how individuals with disabilities in Shanghai perceive the accessibility of public spaces and their experiences of various barriers in transit to public spaces. We conducted semi-structured, in-depth interviews with community-dwelling individuals with mild to severe physical, sensory, and multiple disabilities ( N  = 16). Our findings suggest that despite government efforts to improve accessibility, participants still perceived public spaces to be inaccessible. They encountered physical barriers, social barriers, and unusable accessible facilities in the process of accessing public spaces. Their sense of being a burden to family caregivers also compelled participants to limit their mobility radius. Despite some participants' attempts to advocate for their mobility and accessibility rights, they ultimately chose to compromise when their efforts were not acknowledged. This study seeks to inform policy and practice by increasing understanding of public space accessibility from the perspectives of people with disabilities in urban China. Points of interest: This study is among the first to explore what people with disabilities experience when going to public spaces in urban China, and how they understand these experiences. People with disabilities in Shanghai face various difficulties when going to public spaces. Although there are facilities designed to assist people with disabilities in moving around public spaces in Shanghai, these facilities are often occupied, blocked, or broken, and thus cannot be properly used. Most study participants chose to stay at home and in familiar places to avoid difficulties in going to public spaces and burdening their family members. Participants who tried to advocate for their rights gave up after their efforts were not responded to. Policymakers and practitioners should understand the difficulties of people with disabilities and their families when they go to public spaces and include them when developing and implementing relevant policies and services.